Is a More Comprehensive Surgery Necessary in Patients With Uterine Serous Carcinoma?. Issue 7 (September 2015) - Touhami, Omar; Trinh, Xuan-Bich; Gregoire, Jean; Sebastianelli, Alexandra; Renaud, Marie-Claude; Grondin, Katherine; Plante, Marie
<x xml:space="preserve">Abstract</x> Objective Uterine serous carcinoma (USC) is an aggressive histologic subtype of endometrial cancer that shares similarities to serous ovarian cancer, with a propensity for spread to the upper abdomen, a high recurrence rate, and a poor prognosis. The aim of this study was to determine whether the traditional surgical staging procedure for endometrial cancer was adequate for USC or whether a more extensive surgery, similar to the staging procedure for ovarian cancer, needs to be performed. Specifically, the roles of omentectomy and sentinel lymph node (SLN) mapping were evaluated. Methods We retrospectively identified cases of presumed clinical stage I USC at our institution from April 2005 to March 2014. Medical records were reviewed for the following information: age at diagnosis, preoperative imaging, operative findings, surgical procedure, and final histology with definitive International Federation of Gynecology and Obstetrics stage. Results A total of 39 patients with presumed clinical stage I USC were identified. According to the final pathology report, the surgical stage was as follows: 17 stage IA (44%), 8 stage IB (20%), 3 stage II (8%), 2 stage IIIA (5%), 6 stage IIIC1 (15%), 1 IIIC2 (3%), and 2 stage IVB (5%). Therefore, 14 patients (36%) were surgically upstaged, but none of the patients had their clinical disease upstaged by virtue of finding microscopic metastatic disease in an otherwise normal-looking omentum. Sentinel lymph node mapping was performed in 19 patients (42%). Sensitivity and negative predictive value of SLN mapping were 100% when at least 1 SLN was identified. Conclusions The detection of microscopic disease in radiologically and clinically normal-appearing omentum seems to be rare in USC. Sentinel lymph node mapping seems to be valuable in the serous subtype of endometrial cancer. A less extensive surgery may be possible in patients with USC as it seems to provide the same information as a more extensive surgery.